Upaya Peningkatan Kebersihan Gigi Anak Usia Sekolah melalui Edukasi dengan Media Poster - Muhammad Faisal; Eka Susanti; Dewi Susanti; Dewi Rosmalia (CV. CENDIKIA JENIUS INDONESIA, 2025)
This community service program aimed to improve the dental and oral hygiene of school-age children at SDN 12 Puhun Pintu Kabun, Mandiangin Koto Selayan District, Bukittinggi City, through education using poster media. The implementation method consisted of three main stages: preparation, implementation, and evaluation. The implementation stage included oral health education, demonstrations of proper tooth brushing techniques using the “4 Right 5 Perfect” principle, and hands-on practice with a disclosing solution made from red dragon fruit extract to identify uncleaned tooth areas. Evaluation was carried out through pre-test and post-test assessments to measure knowledge improvement and Hygiene Index (HI) examinations before and after the activity. The results showed a significant increase in students’ oral hygiene, with good dental cleanliness rising from 58% to 94%, and good knowledge increasing from 51% to 96%. The program also successfully established new habits of brushing teeth twice daily using the correct technique. In conclusion, this community service program effectively improved children’s oral health knowledge and behavior through interactive education and hands-on learning using poster-based media.